"This isn’t Just about Me!”: A Collaborative Autoethnographic Inquiry into EFL Learners’ Social Awareness Construction - Anggraini, Nurul; Setyarini, Sri; Nurfaidah, Sitti; Musaldin, La Ode; Mauliani, Sri (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2025)
In recent years, foreign language learning, especially English, has evolved from a purely academic focus to fostering social awareness, particularly in rural Indonesian areas where cultural barriers and stereotypes are prevalent. Anchored by collaborative autoethnography (CAE), this qualitative study reflects on our lived critical incidences as EFL learners from rural areas in Indonesia for more than a decade. This study depicts how we, as EFL learners and teachers at the same time, perceive English learning, which develops our linguistic abilities and literacies to contribute to the local communities. Through critical reflection we found that honing linguistic abilities or the English language did not merely develop the language skill, but it reconstructed EFL learners' social awareness. In this way, as rural EFL learners, we placed ourselves as the agents of change who are in charge of promoting cultural reformation, education development, and global community collaboration.